Ø£Ø«Ø± Ø®Ù„ÙÙŠØ§Øª Ù…Ø¯Ø±Ø³ÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ ØØµÙŠÙ„Ø© ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¨Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ù…Ù†Ø·Ù‚Ø© Ø³ÙƒØ±Ø¨ÙŠÙ„Ø§ Ø¨Ù…Ø§ØªØ±Ø§Ù… - Siti Ainun; Dedy Wahyudin; Suparmanto Suparmanto (Lughatu Ad-Dhat, 2022)
the influence of the teacher's educational background of the Arabic language teachers on the Arabic language learning outcomes of MTs students throughout the Sekarbela district, which aims to find out the influence of the teacher's educational background on student learning outcomes. The research is a quantitative research technique used is survey research using Descriptive, while data collection is done by taking value data directly from the teacher in the field of Arabic studies, questionnaires and documentation. The object of research is all MTs students in the Sekarbela district as the population and the sample is taken at random 100 people. The research data obtained the scores of student learning outcomes taught by teachers with an Arabic educational background obtained the highest value was 93 and the lowest value 77 with an average of 82.85 and standard deviation of 4.671 and standard error 1.044. While the score of student learning outcomes taught by teachers with a background not in Arabic education was obtained the highest value was 88 and the lowest value of 72 with an average of 78,55 and a standard deviation of 3,649 and an error standard of 0,816. Based on calculations using the t test obtained thitung = 3,31 and at a significant level of 5% obtained ttable = 1,99 and a significance level of 1% t table = 2.63 thus 1,99 < 3,31 > 2.63. So that Ha is accepted, meaning that there is a significant influence between the teacher's educational background on the learning outcomes of MTs students throughout the Sekarbela district. This shows the influence of the background of teacher education on students Arabic learning outcomes strong effectiveness to student learning outcomes.